1956
DOI: 10.1029/tr037i005p00558
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the equatorial countercurrent in the central Pacific

Abstract: Cruise 15 of the M.V. Hugh M. Smith consisted of four consecutive lines of oceanographic stations along 140°W longitude between 8°N and 7°S latitude. Geostrophic calculations show that during a five‐week period the maximum eastward velocity component in the Countercurrent progressively increased from 63 to 120 cm/sec and the volume of flow increased from 18.3 to 22.6 X 106 m3/sec.In spite of these short‐term variations, the Equatorial Countercurrent in the central Pacific is remarkably predictable in latitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1959
1959
1967
1967

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Op decrease in velocity in the thermocline and the tendency for the maximum velocity to occur near the middle of the mixed layer (Figs. 2 and 3) [Sverdrup, 1932;Jerlov, 1956;Austin, Stroup, and Rinkel, 1956; and others]. From a comparison of individual sections it would appear that the short-period changes in the surface currents as measured by the GEK are also approximately geostrophic (Fig.…”
Section: Ov Ov Ov Ovmentioning
confidence: 99%
“…Op decrease in velocity in the thermocline and the tendency for the maximum velocity to occur near the middle of the mixed layer (Figs. 2 and 3) [Sverdrup, 1932;Jerlov, 1956;Austin, Stroup, and Rinkel, 1956; and others]. From a comparison of individual sections it would appear that the short-period changes in the surface currents as measured by the GEK are also approximately geostrophic (Fig.…”
Section: Ov Ov Ov Ovmentioning
confidence: 99%
“…Montgomery and Stroup [1962] quote transports between 9 and 48 million m3/sec, and they state that it still remains unknown how the flow varies with season and longitude. Austin et al [1956] have shown that transports may vary considerably within a few weeks. '…”
mentioning
confidence: 99%